EVALUASI PROGRAM KELUARGA BERENCANA DALAM PARTISIPASI METODE PRIA DI KECAMATAN JATIPURO KABUPATEN KARANGANYAR - Apta Fairuz Syahadiva; Dyah Lituhayu; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
The male family planning program is an alternative for people who cannot participate in the female family planning program and to overcome the problem of population explosion in Indonesia. The participation of men in Karanganyar Regency is quite good, which is above 5%, while in Jatipuro District it is quite low, which is below 5%. Departing from these problems, this research aims to evaluate and socio-cultural factors of the family planning program in the participation of men's methods in Jatipuro District, Karanganyar Regency. This research uses descriptive qualitative method with snowball sampling technique. The results of research that the role of government agencies in the success of the male family planning program was good can be seen from William Dunn's indicators, that is, effectiveness, efficiency, adequacy, equity, responsiveness and appropriateness. Community participation in Jatipuro Subdistrict, Karanganyar Regency itself is still minimal due to social factors in term of the perception and cultural factors in term of knowledge of the community to the role of family. Therefore, the male family planning program is considered not successful in achieving the goal of increasing male participation. The government should strive to promote through community activities such as wayang kulit, community service and others, try to make new breakthroughs in contraceptives and society especially men who have participated as agents of change in providing motivation to men who have not participated in the family planning program.